Compliance With Fisheries Regulations in the Persian Gulf, Islamic Republic of Iran - Karimi Goghari, Daryoush (2002)
Noncompliance behaviour of Iranian fishers with the fisheries regulations in the Persian Gulf is examined in this study. A formal theoretical model and analytical framework that was useful in the understanding of compliance behaviour of individuals with fisheries regulations are developed. By using a standard questionnaire and a stratified random sampling method, a total of 566 fishermen from three Iranian provinces located on the coast of the Persian Gulf were interviewed. The factors include deterrence, moral, social influences and legitimacy variables that can explain the observed noncompliance with zoning regulation for shrimp fishery were examined. A Probit and Logit econometric techniques were used to estimate the violation decision by Iranian fishermen in the study area while the Tobit model was used to estimate the total number of fishing days in Shrimp Fishing Zone (SFZ). The model was classified into two types: the basic and the extended model. In general, the Probit estimation technique perfonns better than the Tobit technique. The Probit model exogenous probability variables however gives better results than the Probit model using raw probabilities. The results indicated that deterrence, moral, and legitimacy factors determined the violation decision of individual fishers to fish in the prohibited zone. The social influence factor (PERTVIOL) was only significant in the Bushehr province. The results also indicate that the deterrence variables, moral development, and legitimacy factor are more important than the social influence factor in explaining the compliance behaviour in the study area. From the economic perspective, moral development and legitimacy variables can complement the efficiency goal in any enforcement program by reducing the need for large expenditures on enforcement inputs to secure compliance. The results showed that using exogenous variables directly in the extended model to explain the violation decision in the individual provinces provide a good result for provinces of Khuzestan and Busbehr. The number of Fishing days (DAY) appears to play a very important role in explaining the violation decision of fishermen in the Khuzestan and Busbehr provinces. The other important variables are the horsepower of fishermen boats (POWER), the morality variable (MeODE), and number of times that fishermen have seen the enforcement personnel at the sea (FBOATNO). The legitimacy variables also have considerable role in explaining compliance behaviour in the cases of Khuzestan and Busbehr provinces. Although the overall probability of detection and conviction (OVEPROB) variable was significant with an unexpected sign, the exogenous variables of probability of detection and conviction came out significant in most the regressions runs with expected signs. It cannot be denied that it plays a very important role than the other (such as moral obligation and legitimacy) variables in securing compliance. Thus, enforcement resources should be utilized together with positive reinforcement of the normative variables. Nevertheless, enforcement inputs wi)) have a deterrence effect on the violators and other fishermen thus reducing the overall violation rate. The capacity of enforcement resources in the Persian Gulf area is limited. There is need to reestablish the enforcement institutions and resources. The government should therefore pay attention to enhancing enforcement resources in the area of study to deter violators.